Analisis Kegiatan Belajar Mengajar Dengan Sistem Daring Di Masa Pendemi Covid-19 Di SMK Favorit Pungging Kabupaten Mojokerto - Syafa'at, Wahyu; Nahdly, M. As'ad (Al-Muttaqin : Jurnal Studi, Sosial, dan Ekonomi, 2021)
The Covid-19 pandemic has a considerable impact and affects psychological conditions and changes in human behavior over a long period of time. One of them is having an impact on the world of education in Indonesia. Teachers and students are required to be able to carry out distance learning activities. Vocational High Schools implement teaching and learning activities that are carried out online based on a circular from the East Java Provincial Government through the East Java Provincial Education Office. This study aims to analyze teaching and learning activities with an online system during the Covid-19 pandemic at SMK Favorit Pungging, Mojokerto Regency. This study used a descriptive method with a qualitative approach with informants consisting of teachers and students at SMK Favorit Pungging, Mojokerto Regency. Based on the results of the research, it can be seen that teaching and learning activities carried out during the Covid-19 pandemic at SMK Favorit Pungging, Mojokerto Regency used an online system with applications in the form of: zoom, whatsapp, google classroom, and youtube. Online learning runs smoothly, even though it is not ideal. The learning outcomes of students vary, ranging from unsatisfactory, quite satisfying to very satisfying. The obstacles faced by students and teachers in online learning include: the availability of supporting tools such as devices and laptops, the availability of internet quotas, and an unstable network. If applied during the Covid-19 pandemic, online learning is considered quite effective, but it must be supported by a more varied learning model so that it remains attractive if used in the long term. Keywords: Teaching and Learning Activities, Online Systems, Covid-19 Pandemic Period